(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This scientific article analyzes the effect of the combination of chitosan and whey powder in poultry and in biological systems in general on calciumphosphorus metabolism, osteoblast activity, and bone mineralization. Chitosan, as a polysaccharide with high sorption ability and ion-binding capacity, may reduce intestinal calcium absorption when applied at high doses. In contrast, whey powder—rich in bioactive peptides, lactose, and minerals—enhances calcium uptake from the intestine, stimulates collagen synthesis in osteoblasts, and supports bone mineral density. The overall efficiency of the combination is dose-dependent: optimal proportions contribute to metabolic homeostasis, bone tissue strengthening, and improved mineral balance, whereas excessive chitosan may induce mineral deficiency